(untitled) (Baghdad Science Journal, 2005)
In this research study theory to find the stress and emotion gases in the glass as a result of exposure to pulses of the laser beam has been the study using vehicles three major on-system axes cylindrical (r, 0, z), where I took three models of glass silica glass soda glass fused and shedtwo types of lasers where the study showed that the thermal stresses and emotions ...